"Efecto del acetiluro de calcio sobre la maduración de fruta en dos cultivares de plátano (Musa paradisiaca L.)". - Merchan Sánchez, Byron Raúl (2020)
The main objective of the research was to analyze the use of calcium acetyluride in banana fruits (Musa paradisiaca L.), corresponding to the varieties Dominico and Barraganete. For the trial a completely randomized design (DCA) with trifactorial arrangement A x B x C was used, with twelve treatments and three repetitions, for the determination of differences between means the Tukey al test was used (p≤ 0.05). The variables evaluated were: ripening time, dry matter content, moisture, pH, energy, brix degrees, acidity, pulp hardness, dry matter of the shell, shell moisture and shell color. In relation to the results obtained, it could be highlighted that, independently of the variety both in physical and qualitative parameters in fruit pulp, all the treatments exposed to calcium acetyluride (T1, T2, T3, T4, T5, T6, T7 and T8) stood out. However, it is important to note that within chemical parameters such as energy and dry matter content, the controls T9 and T11 respectively stood out. However, despite this, there was a marked influence of calcium acetyluride as an artificial ripening agent, overcoming the natural ripening in the other aspects evaluated, especially in the variable ripening time, where the treatments exposed to acetyluride were able to obtain an advantage of more than 50% of the time taken by the controls to ripen. Keywords: Climatic fruit, artificial ripening, acetylene, quality, shelf life